Isolation, identification and optimization of a new extracellular lipase producing strain of rhizopus sp. - Kantak, Jayshree B.; Bagade, Aditi V.; Mahajan, Siddharth A.; Pawar, Shrikant P.; Shouche, Yogesh S.; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2011)
A lipolytic mesophilic fungus which produces lipase extracellularly was isolated from soil. Based on ITS1-5.8S-ITS4 region sequences of ribosomal RNA, it was concluded that the isolate JK-1 belongs to genus Rhizopus and clades with Rhizopus oryzae. The present paper reports the screening, isolation, identification, and optimization of fermentation conditions for the production of lipase (EC 3.1.1.3). Culture conditions were optimized, and the highest lipase production was observed in basal medium with corn steep liquor as nitrogen source and glucose as carbon source. Maximum lipase production was observed at 72 h, which is about 870 U/ml. Optimization of fermentation conditions resulted in 16-fold enhancement in enzyme production.
Keywords: Corn steep liquor; Fermentation; ITS region; Lipase; Medium optimization; Rhizopus

Characterization of roseomonas and nocardioides spp. for arsenic transformation - Bagade, Aditi V.; Bachate, Sachin P.; Dholakia, Bhushan B.; Giri, Ashok P.; Kodam, Kisan M. (Journal of Hazardous Materials, 2016)
The metalloid arsenic predominantly exists in the arsenite [As(III)] and arsenate [As(V)]. These two forms are respectively oxidized and reduced by microbial redox processes. This study was designed to bioprospect arsenic tolerating bacteria from Lonar lake and to characterize their arsenic redoxing ability. Screening of sixty-nine bacterial species isolated from Lonar lake led to identification of three arsenic oxidizing and seven arsenic-reducing species. Arsenite oxidizing isolate Roseomonas sp. L-159a being closely related to Roseomonas cervicalis ATCC 49957 oxidized 2 mM As(III) in 60 h. Gene expression of large and small subunits of arsenite oxidase respectively showed 15- and 17-fold higher expression. Another isolate Nocardioides sp. L-37a formed a clade with Nocardioides ghangwensis JC2055, exhibited normal growth with different carbon sources and pH ranges. It reduced 2 mM As(V) in 36 h and showed constitutive expression of arsenate reductase which increased over 4-fold upon As(V) exposure. Genetic markers related to arsenic transformation were identified and characterized from the two isolates. Moderate resistance against the arsenicals was exhibited by the two isolates in the range of 1-5 mM for As(III) and 1-200 mM for As(V). Altogether we provide multiple evidences to indicate that Roseomonas sp. and Nocardioides sp. exhibited arsenic transformation ability. (C) 2016 Elsevier B.V. All rights reserved.